개방형주차장의 소방설비 개선 제안 - 정기신(Jeong, Keesin) (한국화재소방학회 논문지, 2016)
In cars, the amount of combustibles, such as plastics, textiles, etc., have increased dramatically to improve the fuel efficiency of cars by reducing the gross vehicle weight according to the increases in an oil price and to reduce environmental problems. One or two cars were involved in a parking lot fire prior to the mid-2000 s. On the other hand, there were many parking lot fires where the entire car was destroyed due to increasing the use of plastics. In this study, the quantity of combustibles in a car was 316.2 kg over a total weight 1935 kg. This is 16.34% of total weight and 10 times greater than that three decades earlier. When a sprinkler is installed as a parking lot fire protection system as a substitute for water spray, the water discharge of the sprinkler must maintain the original density of water spray, $20lpm/m^2$. In addition, the use of a hose reel $CO_2$ system at pilotis parking lots must be prohibited because the hose reel $CO_2$ system has no adaptability for a car fire. Instead, this study proposes foam, dry powder, loaded stream systems be used in parking lot fire suppression systems. 유가의 상승과 환경의 문제로 차량중량의 감소에 의한 차량연비를 개선하기 위하여 가연물인 플라스틱과 직물 등의 사용이 획기적으로 증대되어 주차장에서 화재가 발생하면 2000년대 중반 이전에는 한 두 대가 연소되고 마는 것과는 달리 주차된 차량 전체가 연소하는 화재가 많이 발생하였다. 본 연구에서 차량에 사용되는 플라스틱 등 가연물의 량을 확인한 결과 한 대에 316.2 kg으로 차량 전체무게 1935 kg 대비 16.34%가 되어 과거대비 10배 이상의 증가가 있었다. 또한 주차장의 소화설비로 스프링클러를 설치 시 물분무설비의 원래 성능대로 살수밀도를 $20lpm/m^2$를 사용할 것과 필로티 주차장에 호스릴이산화탄소소화설비 대신 적응성이 있는 포, 분말, 강화액 설비를 사용할 것을 요구하였다.